Extra-thoracic rupture of giant subclavian artery aneurysm. (13th April 2021) - Savlania, Ajay; Jain, Prashant; Thakur, Uttam Kumar; Singh, Charan
Abstract: Subclavian artery aneurysms are rare, but they are frequently responsible for limb or life-threatening complications. The clinical presentation, as supraclavicular mass to rupture, has been reported in literature, with management strategies being endovascular intervention to open conventional surgery. We report a case of giant subclavian artery aneurysm measuring 10 cm × 12 cm, which presented with a large anterior chest wall lump and massive bleed to our emergency department. We successfully treated this patient by ligating the aneurysm and evacuating the chest wall haematoma.